2018
DOI: 10.1242/jeb.189167
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-beta 1 (TGF-β1) induces the differentiation of rainbow trout (Oncorhynchus mykiss) cardiac fibroblasts into myofibroblasts

Abstract: The collagen content of the rainbow trout heart increases in response to cold acclimation and decreases with acclimation to warm temperatures. This ability to remodel the myocardial extracellular matrix (ECM) makes these fish useful models to study the cellular pathways involved in collagen regulation in the vertebrate heart. Remodelling of the ECM in the mammalian heart is regulated, in part, by myofibroblasts which arise from pre-existing fibroblasts in response to transforming growth factor-β1 (TGF-β1). We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…Col III expression was significantly increased 24 h after TGF-β1 treatment and significantly decreased 6, 12 and 24 h after MG132 and TGF-β1 treatment compared with the control group (all P<0.05). The results indicated that 2.5 µM MG132 decreased the mRNA levels of fibrosis-associated factors following stimulation with 5 ng/ml TGF-β1, which causes the fibroblasts to differentiate into myofibroblasts associated with fibrotic processes ( 21 ).…”
Section: Resultsmentioning
confidence: 99%
“…Col III expression was significantly increased 24 h after TGF-β1 treatment and significantly decreased 6, 12 and 24 h after MG132 and TGF-β1 treatment compared with the control group (all P<0.05). The results indicated that 2.5 µM MG132 decreased the mRNA levels of fibrosis-associated factors following stimulation with 5 ng/ml TGF-β1, which causes the fibroblasts to differentiate into myofibroblasts associated with fibrotic processes ( 21 ).…”
Section: Resultsmentioning
confidence: 99%
“…The transcript levels of the target genes, col1a3, mmp-2, mmp-9, mmp-13 , were measured at multiple time points to establish a timeline of the cellular response during remodelling with respect to the signalling protein kinases and acclimation time. The primers used were those previously described by Johnston and Gillis (2018). ef1α and β-actin were determined to be the most suitable reference genes using the program GeNorm (Vandesompele et al, 2002).…”
Section: Methodsmentioning
confidence: 99%
“…The purpose of the present study was to determine if thermal acclimation of rainbow trout activates the MAPK signalling pathway, which is hypothesized to be responsible for initiating temperature induced cardiac remodelling. Building from our in vitro studies (Johnston and Gillis, 2020; Johnston et al 2019; Johnston and Gillis 2018; Johnston and Gillis, 2017), we specifically hypothesized that cold acclimation (4 °C) would cause an increase in the phosphorylation status of p38 MAPK and ERK, and induce changes in the expression of gene transcripts that would support an increase in collagen deposition. It was also hypothesized that warm acclimation (18 °C) would have the opposite effect.…”
Section: Introductionmentioning
confidence: 99%
“…Average normalized collagen protein levels between control, nonsense siRNA-and miR-29b-transfected groups were analysed with a one-way ANOVA at a confidence interval of 95%. For each treatment, n=3, where n represents a cell culture established from the same ventricle of a male rainbow trout, as previously described (Johnston and Gillis, 2018).…”
Section: Statistical Analysis Of Treated Cellsmentioning
confidence: 99%